Importance of the code of ethics in the organization - Jordanova, E. (Економічний вісник Донбасу, 2014)
Counteracting the unethical actions and influencing the behavior of the human factor towards ethical behavior must be a priority of a company’s policy. The research and recommendations in this direction outline the necessity of an Ethic code that shall comprise individual and company values, and whose harmonious interaction shall provide stability and efficiency of the management process. This code shall serve as a balancing force among the various interests and systems of values, which shall thus establish common ethical standards of behavior.